1964
DOI: 10.1029/jz069i012p02423
|View full text |Cite
|
Sign up to set email alerts
|

An interpretation of Schröter's Valley and other lunar sinuous rills

Abstract: Several more or less unsatisfactory theories have been proposed for the origin of lunar sinuous rills such as Schröter's Valley. This paper presents a new explanation of the formation of these rills, namely, that they are valleys eroded by nuées ardentes. Characteristics of the rills, including form and association, are cited in support of this theory. Supporting evidence is found in the similarity of the rills to furrows eroded by nuées ardentes on the earth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Cameron (1964) suggested that fluidised ash flows could have carved rilles in events similar to terrestrial nures ardentes. There was some evidence that lava flows existed on the lunar surface from Earth-based observations (Strom and Fielder, 1970) and the photographs returned by Ranger and Orbiter satellites gave strong confirmation that volcanic activity had occurred on the Moon.…”
Section: Rilles As Volcanic Featuresmentioning
confidence: 97%
“…Cameron (1964) suggested that fluidised ash flows could have carved rilles in events similar to terrestrial nures ardentes. There was some evidence that lava flows existed on the lunar surface from Earth-based observations (Strom and Fielder, 1970) and the photographs returned by Ranger and Orbiter satellites gave strong confirmation that volcanic activity had occurred on the Moon.…”
Section: Rilles As Volcanic Featuresmentioning
confidence: 97%
“…Visual observations may achieve some improvement over this The enormous effort exerted to deliver astronauts limit under favorable circumstances but the effective to the lunar surface, and return them safely to Earth, ground resolution for photographic plates, the princi-ple data source for published lunar geomorphic studies prior to the advent of spacecraft data, can be considered to be approximately 1 km. Telescopic photographs of the Moon led to several proposed mechanisms for the origin of the sinuous rilles (summarized in Cameron, 1964;Mutch, 1970, pp. 190-196).…”
Section: Telescopic Studiesmentioning
confidence: 99%
“…The water required for this mechanism was consistent with a proposed model that advocated an extensive lunar hydrosphere early in the history of the Moon (Gilvarry, 1960). Published alternative mechanisms for sinuous rille formation included collapsed lava tubes or lava channels (Baldwin, 1963), erosion by pyroclastic flows (Cameron, 1964), and a combination of faulting and subsidence (Quaide, 1965). Cameron (1964) and Quaide (1965) cite the Hadley Rille (Fig.…”
Section: Telescopic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cameron (1964) suggested that the rilies were formed by erosion by nuées ardentes. Urey (1967), Gilvarry (1968), and Lingenfelter ei al.…”
Section: Introductionmentioning
confidence: 99%